Application Of The Blockchain Technology Within Healthcare - Lin, Michelle Hwei Yee (2021)
Blockchain technology is an advanced technology that was initially used in the cryptocurrency field and now it has been extensively being implemented in various industries and fields. In this project, the potential of blockchain implementation in the healthcare industry is figured out and the area of study is focused on the COVID-19 related matters. In order to help with the situation of COVID-19 pandemic, a predictive model on the infected patient’s severity level is constructed. The predictive model is used to forecast the severity level of a person who is infected with COVID-19 virus based on his various symptoms. In this project, a Logistic Regression statistical model is developed by using Python to construct the proposed model. Python is a popular programming language that is widely used in the area of artificial intelligence and it also has plenty of libraries that are used to build various predictive models. Besides that, a blockchain-based framework that focused on the Electronic Medical Record (EMR) is proposed. A broad study of journal papers on the blockchain framework is being carried out in order to have a basic understanding on the blockchain technology. The idea of the EMR framework with the blockchain-based application and database system is developed. Patients, hospital providers, healthcare authorities, financial parties, and the Certificate Authority are among the five groups of participants involved in the proposed framework. There are four proposed algorithms based on the actions of viewing and writing EMR, as well as another two additional actions aimed at improving the security of the blockchain framework. Finally, the constructed predictive model is implemented along with the proposed application, which connects all groups of participants with the blockchain-based EMR system.